The Influence Of Product Quality, E-Wom, Brand Image On Purchase Decision With Price Discount As A Moderating Variable - Destia; Sartika, Dewi (MBIA, 2025)
The increasing intensity of competition in online business encourages companies to understand the factors that influence consumer purchasing decisions, particularly in digital markets. This study aims to analyze the effect of product quality, electronic word of mouth (E-WOM), and brand image on purchase decision, with price discount as a moderating variable among Aldes Watch consumers. This research is grounded in the Theory of Planned Behavior (TPB), which explains that consumer behavior is driven by intentions shaped by attitudes, subjective norms, and perceived behavioral control. A quantitative research approach was employed by collecting data through questionnaires distributed to 72 Aldes Watch consumers selected from a population of 256 consumers using a simple random sampling technique. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that product quality, E-WOM, and brand image have a positive and significant effect on purchase decision. Furthermore, price discounts are proven to strengthen the influence of product quality, E-WOM, and brand image on purchase decision. These findings suggest that price discounts function as an effective marketing strategy in enhancing product attractiveness and reinforcing consumers’ perceptions of quality and brand image. The implications of this study highlight the importance for online business actors to integrate product quality improvement, positive E-WOM management, brand image strengthening, and strategic price discount implementation to enhance purchasing decisions and maintain competitiveness in the digital era. Keywords: Quality,  e-wom, Brand Image, Discount, Purchase Decision Abstrak Meningkatnya intensitas persaingan dalam bisnis online mendorong perusahaan untuk memahami faktor-faktor yang memengaruhi keputusan pembelian konsumen, khususnya di pasar digital. Penelitian ini bertujuan untuk menganalisis pengaruh kualitas produk, electronic word of mouth (E-WOM), dan citra merek terhadap keputusan pembelian, dengan diskon harga sebagai variabel moderasi pada konsumen Aldes Watch. Penelitian ini didasarkan pada Theory of Planned Behavior (TPB) yang menjelaskan bahwa perilaku konsumen didorong oleh niat yang dibentuk oleh sikap, norma subjektif, dan persepsi kontrol perilaku. Pendekatan penelitian kuantitatif digunakan dengan mengumpulkan data melalui kuesioner yang disebarkan kepada 72 konsumen Aldes Watch yang dipilih dari populasi sebanyak 256 konsumen menggunakan teknik simple random sampling. Data dianalisis menggunakan Structural Equation Modeling–Partial Least Squares (SEM-PLS). Hasil penelitian menunjukkan bahwa kualitas produk, E-WOM, dan citra merek berpengaruh positif dan signifikan terhadap keputusan pembelian. Selain itu, diskon harga terbukti memperkuat pengaruh kualitas produk, E-WOM, dan citra merek terhadap keputusan pembelian. Temuan ini menunjukkan bahwa diskon harga berfungsi sebagai strategi pemasaran yang efektif dalam meningkatkan daya tarik produk serta memperkuat persepsi konsumen terhadap kualitas dan citra merek. Implikasi penelitian ini menekankan pentingnya bagi pelaku bisnis online untuk mengintegrasikan peningkatan kualitas produk, pengelolaan E-WOM yang positif, penguatan citra merek, serta penerapan strategi diskon harga yang tepat guna meningkatkan keputusan pembelian dan mempertahankan daya saing di era digital. Kata Kunci: Kualitas, e-wom, Citra, Diskon , Keputusan Pembelian